Dorsal offset rhinoplasty for treatment of stenotic nares in 34 brachycephalic dogs. Issue 8 (27th August 2020) - Dickerson, Vanna M.; Dillard, Corinne M. B.; Grimes, Janet A.; Wallace, Mandy L.; McAnulty, Jonathan F.; Schmiedt, Chad W.
Abstract: Objective: To describe the technique, outcome, and owner satisfaction associated with dorsal offset rhinoplasty (DOR) to treat stenotic nares in brachycephalic dogs. Study design: Retrospective case series. Animals: Thirty‐four client‐owned dogs. Methods: Medical records of dogs treated with DOR at a veterinary teaching hospital over a 6‐year period were identified. Dorsal offset rhinoplasty was defined as removal of a dorsal wedge of nasal planum from each naris with apposition of the rostral abaxial tissue to the caudal axial tissue, resulting in translocation of the alar cartilage in both median and dorsal planes. Immediate and postoperative complications were recorded. Owners were asked to report any complications with healing of the nares and to score their satisfaction with the appearance of the nares. Results: Thirty‐four dogs met the inclusion criteria. Twenty‐nine (85%) dogs were examined a median of 402.5 days (range, 23‐2042) postoperatively, with no major complications related to the rhinoplasty recorded. Eighteen owners responded a median of 701 days (range, 37‐1622) postoperatively. One owner reported that self‐trauma led to collapse of one naris. One owner reported collapse of both nares within 4 years; timing and cause were unknown. Sixteen of 17 responding owners reported that they were very satisfied with the outcome of the rhinoplasty. The owner of the dog with the collapsed naris was very unsatisfied. One owner did not provide a satisfaction score. Conclusion: Owners were generally highly satisfied with DOR, and complications were uncommon. Clinical significance: This report describes an alternate technique to treat stenotic nares.